ANALISIS PENGGUNAAN TATA BAHASA DALAM PENYUSUNAN DOKUMEN PENAWARAN PROYEK KONTRUKSI PEMBANGUNAN GEDUNG FAKULTAS TEKNIK UPN “VETERAN” JAWA TIMUR - Larasati, Agistya Rachma; Ilham, Muhammad Nur; Jatmiko, Muhammad Fauzi; Wijianto, Yoga Pratama; Abidin, Farhan Zainul; Sholihatin, Endang (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
This research analyzes the use of grammar in the preparation of project proposal documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java. The use of clear, accurate, and rule-compliant grammar is crucial to ensure transparency, fairness, and efficiency. The objectives of this research are to: 1) Identify the grammar used in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java; 2) Identify the strengths and weaknesses of language selection in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java; and 3) Provide recommendations for improvements to address writing errors in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java. This study employs a descriptive qualitative method, using descriptive data from documents and indirect interviews conducted via Google Forms. The conclusions of this research are: 1) The grammar used in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java is composed of sentences that are easy to understand and persuasive, referencing data aimed at helping to avoid misunderstandings and ensuring a common understanding among all parties involved in the tender process. However, there are several writing errors that do not conform to EYD (Enhanced Spelling System). There are a total of 112 data errors, including words and sentences in the documents of the first and third-place winners of the tender competition, comprising 43 typographical errors, 4 inconsistencies in terminology, 36 foreign language writing errors, 3 incorrect word choices, 9 preposition usage errors, and 17 non-standard word usages; 2) There are strengths and weaknesses in the language selection in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java, including sentences that are advantageous and disadvantageous in the tender process. The research results show that out of 120 respondents, 104 (87.26%) answered that the language selection was advantageous and 16 (12.74%) answered that it was disadvantageous. Therefore, it can be concluded that good grammar use significantly affects construction project tenders; and 3) The recommendations for improvement to address writing errors in the tender documents for the construction of the Faculty of Engineering Building at UPN "Veteran" East Java are: a) When writing documents, it is recommended to follow the Indonesian Dictionary (KBBI) and EYD to ensure that readers can easily understand the content and avoid misunderstandings. b) During the document writing process, it is hoped that the writer remains focused to prevent errors. c) Before finalizing the documents, it is recommended to recheck the content using spelling and grammar tools. Keywords: Grammar, efficient, document, tender.